Antibacterial activity of extract sangkareho leaves (Callicarpa longifolia LAM.) on Salmonella typhi and Staphylococcus epidermidis - Silvani Permatasari; Ervi Audina Munthe; Muntir Guru Singa; Elsa Trinovita; Ratna Widayati; Natalia Sri Martani; Anna Marthea Veronica (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: The most commonly found disease-causing microorganisms are the Salmonella typhi and Staphylococcus epidermidis bacteria. S.typhi is a gram-negative bacterium that causes typhoid fever, and S.epidermidis is a gram-positive bacterium that attacks mucous membranes and human skin. Sangkareho (Callicarpa longifolia Lam.) is one of the indigenous herbal plants of Central Kalimantan, which is empirically used as a wound medicine, diarrhea, diabetic, anti-inflammatory, and can be an antibacterial agent.Objective: This study used six groups are concentrations of 10%, 25%, 50%, and 100%, Chloramphenicol as a positive control, and dimethyl sulfoxide (DMSO) as a negative control. Methods: The method used for this test is the well diffusion method. In Nutrient Agar (NA) media, holes were made to insert 40 μl of each extract concentration, positive and negative control with four repetitions, then incubated for 18-24 hours at 37ºC. Data analysis using the One Way Anova test.Results: The research findings showed that ethanol extract of sangkareho leaves with all concentrations had an inhibitory effect against both bacteria tested.Conclusion: The ethanol extract of sangkareho leaves at the concentration of 10% was found to be the optimum and at the concentration of 100% was the maximum effectiveness for inhibiting S. typhi and S. epidermidis.